Herbal Medicines in management and prevention of COVID-19 - Ritav Viralbhai Brahmbhatt (International Journal of Phytomedicine, 2021)
Traditional herbal medicines are widely accepted in the world. Certain countries and WHO have research investment in traditional herbal medicines. COVID-19 came as a major Health care challenge for human in 2019. 480 deaths have been recorded till 18th of April 2020 in India. No pharmaceutical products have yet been shown to be safe and effective for the treatment of COVID-19. Major 3 types of targets of COVID-19 were identified by researches, which are as follow – 1) Inhibit coronavirus at structural level, 2) Inhibit coronavirus RNA synthesis and replication and 3) Inhibit virulence factor of Coronavirus. Certain Herbal medicines like Tribulus terrestris, Withania somnifera, Curcuma longa, Ocimum sanctum, and Phyllanthus emblica have potent Anti-COVID properties, which is indicating new sunrise in the direction of Herbal medicine.